Four year follow up of fatigue in a geographically defined primary biliary cirrhosis patient cohort. Issue 4 (18th November 2005) - Jones, D E J; Bhala, N; Burt, J; Goldblatt, J; Prince, M; Newton, J L
Abstract : Background and aims: Fatigue is the commonest symptom described by patients in most populations with the autoimmune liver disease primary biliary cirrhosis (PBC), and appears to be unrelated to liver disease severity. At present, it is unclear how the fatigue experienced by patients (only characterised to date in cross sectional studies) evolves over time. In this study, we set out to address how fatigue had changed over four years of follow up in a geographically defined cohort of PBC patients who participated in an earlier cross sectional study of fatigue impact. Methods: Participants in the original 2000 study who were still alive in 2004 were asked to complete the same fatigue assessment tool (fatigue impact score, FIS). In those who had died between 2000 and 2004, medical notes, death certificates, and primary care records were reviewed. Results: A total of 108 of the original cohort of 136 patients were alive at the time of the follow up study, 99 of whom (92%) participated in the follow up study. With the exception of four patients who underwent transplantation between 2000 and 2004, all of whom showed significant improvement in fatigue severity as assessed by FIS, fatigue severity was unchanged over four years of follow up. Among the 28 patients who died during the follow up period, survival was significantly lower in patients who were fatigued at the 2000 baseline (FIS above the median for the whole PBC population (40/160); log rank test, p = 0.006 v non-fatigued patients at baseline). Increased fatigue severity was independently associated with decreased survival on multivariate analysis. Fatigued PBC subjects were significantly more likely to have suffered a cardiac death than non-fatigued patients. Conclusions: The fatigue phenotype appears to be highly stable in PBC. The presence of fatigue in PBC is independently associated with a significantly increased risk of death in general, and cardiac death in particular. Factors underpinning fatigue in PBC, and the mechanisms whereby fatigue is associated with increased mortality, warrant further study.